Mechanical behavior of compacted and stabilized clay with kaolin and cement - Mousavi S. (Jordan University of Science and Technology, 2023)
Bearings (machine parts); Binders; Bins; Cements; Clay; Compaction; Compressive strength; Highway engineering; Kaolin; Portland cement; Shear strength; Silica sand; Soil cement; Soils; Stabilization; Strength of materials; California bearing ratio; Engineering characteristics; Engineering properties; Laboratory investigations; Ordinary Portland cement; Stabilized soils; Standard Proctor compaction; Unconfined compressive strength; Soil testing